Morphology, crystallization, thermal, and mechanical properties of poly(vinylidene fluoride) films filled with different concentrations of polyhedral oligomeric silsesquioxane. Issue 7 (27th November 2012) - Liu, Yizhi; Sun, Yi; Zeng, Fanlin; Chen, Yunjun; Li, Qingkun; Yu, Bowen; Liu, Wenjing
Abstract Nanocomposites consisting of a poly(vinylidene fluoride) (PVDF) matrix and 0–8 wt% fluoropropyl polyhedral oligomeric silsesquioxane (FP‐POSS) were obtained through the solvent evaporation method. Morphology, crystallization, as well as thermal and mechanical properties were investigated. FP‐POSS, acting as a nucleating agent, exhibited robust miscibility with PVDF, enhancing the crystallinity of PVDF. A high relative fraction of the β phase was observed in the composites. The thermal degradation of PVDF was not significantly affected by FP‐POSS under a nitrogen atmosphere. Low addition of FP‐POSS, acting as nanofiller, led to remarkable improvement in mechanical properties, including hardness. The maximum was achieved at 3 wt%. High amounts led to inferior mechanical properties. POLYM. ENG. SCI., 2013. © 2012 Society of Plastics Engineers